PENGUATAN ADMINISTRASI DAN MANAJEMEN PAUD UNTUK MENINGKATKAN MUTU PENDIDIKAN - Fahmi; Rahma Mutiara; Ovi Oktapiani; Nailatus Sa'adah; Pemi Margaret (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early Childhood Education (PAUD) is the primary foundation for developing a child's character, social, emotional, and intellectual abilities. The quality of PAUD education is greatly influenced by the quality of administration and management implemented in educational institutions. Well-organized administration will facilitate the planning, implementation, supervision, and evaluation of educational programs effectively and efficiently. This article aims to discuss the importance of strengthening PAUD administration and management in improving educational quality. The method used is a literature study by reviewing various sources related to PAUD management. The results of the study indicate that strengthening administration includes managing student data, teaching staff, curriculum, facilities, infrastructure, and institutional finances. Meanwhile, good PAUD management includes the functions of planning, organizing, implementing, and evaluating educational programs on an ongoing basis. In addition, the competence of principals and teachers is also a crucial factor in supporting the successful management of PAUD institutions. With professional administration and management, PAUD institutions can create a conducive learning environment, improve the quality of educational services, and optimally support the achievement of early childhood education goals.